Dp412e: a novel human embryonic dystrophin isoform induced by BMP4 in early differentiated cells. Issue 1 (December 2015) - Massouridès, Emmanuelle; Polentes, Jérôme; Mangeot, Philippe-Emmanuel; Mournetas, Virginie; Nectoux, Juliette; Deburgrave, Nathalie; Nusbaum, Patrick; Leturcq, France; Popplewell, Linda; Dickson, George; Wein, Nicolas; Flanigan, Kevin; et al.
Abstract Background Duchenne muscular dystrophy (DMD) is a devastating X-linked recessive genetic myopathy. DMD physiopathology is still not fully understood and a prenatal onset is suspected but difficult to address. Methods The bone morphogenetic protein 4 (BMP4) is a critical signaling molecule involved in mesoderm commitment. Human induced pluripotent stem cells (hiPSCs) from DMD and healthy individuals and human embryonic stem cells (hESCs) treated with BMP4 allowed us to model the early steps of myogenesis in normal and DMD contexts. Results Unexpectedly, 72h following BMP4 treatment, a new longDMD transcript was detected in all tested hiPSCs and hESCs, at levels similar to that found in adult skeletal muscle. This novel transcript named "Dp412e " has a specific untranslated first exon which is conserved only in a sub-group of anthropoids including human. The corresponding novel dystrophin protein of 412-kiloDalton (kDa), characterized by an N-terminal-truncated actin-binding domain, was detected in normal BMP4-treated hiPSCs/hESCs and in embryoid bodies. Finally, using a phosphorodiamidate morpholino oligomer (PMO) targeting theDMD exon 53, we demonstrated the feasibility of exon skipping validation with this BMP4-inducible hiPSCs model. Conclusions In this study, the use of hiPSCs to analyze early phases of human development in normal and DMD contexts has led to the discovery of an embryonic 412 kDa dystrophin isoform. Deciphering the regulation process(es) and the function(s) associated to this new isoform can contribute to a better understanding of the DMD physiopathology and potential developmental defects. Moreover, the simple and robust BMP4-inducible model highlighted here, providing large amount of a longDMD transcript and the corresponding protein in only 3 days, is already well-adapted to high-throughput and high-content screening approaches. Therefore, availability of this powerful cell platform can accelerate the development, validation and improvement of DMD genetic therapies.